Assentamento Carlos Marighella em Poxoréu/MT : circuito espacial de produção da mandioca - Oliveira, Ivan de (2021)
This work had as its object of study the Carlos Marighella Settlement in Poxoréu/MT. In this place, the cultivation of cassava and its processing into flour represents a means to guarantee the families' income and survival. The production of cassava and flour in this settlement has a productive organizational structure based on family farming. This type of agriculture has developed and expanded in Mato Grosso, mainly in rural settlements. Small agricultural producers who develop family farming produce most of the staple foods that reach Brazilians' tables. Among the various foods that are produced by family farming in rural settlements is cassava, which is a food commonly found in various rural settlements such as Carlos Marighella. The cassava that is produced in the Carlos Marighella Settlement has enormous economic importance for small agricultural producers in that area, as it has been, in most cases, the only source of income and survival for the settlers. In this settlement several agricultural activities are developed and each of these activities has its respective spatial production circuits. In this research, we chose to study the spatial circuit of cassava production in the Carlos Marighella Settlement, given that some aspects of this circuit lack a better scientific understanding. The aspects from which the problem was developed are related to the instances of cassava production in its territorial dimension, to the production itself, as well as to the characteristics of its circulation and consumption process. The main objective of the work is to understand the spatial circuit, the cassava producers of the Carlos Marighella Settlement, located in Poxoréu/MT, and its consumers at the Vila Aurora open market, in Rondonópolis/MT. The methodology used for the development of this work is based on bibliographical research, survey and analysis of secondary statistical data and field research. The results obtained in this study reveal that the cassava producers in the Carlos Marighella Settlement are small, low-income family agricultural producers, who produce cassava in a rudimentary way and mainly use private vehicles to transport cassava and flour to open markets from the region or to other trading centers. As for the consumption of cassava, it was found that the main consumers of this product and its derivatives are the poorest portion of the population, which has low income.